2019
DOI: 10.2147/dddt.s204730
|View full text |Cite
|
Sign up to set email alerts
|

<p>Effect of tumor necrosis factor inhibitors on interstitial lung disease in rheumatoid arthritis: angel or demon?</p>

Abstract: Objectives: This study evaluated the correlation between tumor necrosis factor alpha inhibitor (TNF-I) and interstitial lung disease (ILD) in rheumatoid arthritis (RA). We aimed to raise awareness and consummate therapy by summarizing the characteristics of the adverse events of ILD. Methods: A comprehensive search of the PubMed, Embase, Ovid, Cochrane, China National Knowledge Infrastructure, and Wanfang databases was performed from inception to November 2018. Statistical an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 46 publications
1
21
0
3
Order By: Relevance
“…Despite previous concerns over potential pulmonary toxicity with leflunomide, this agent also appears to be potentially beneficial for RA-ILD (62). In the setting of RA-ILD, the choice of biological therapy is not clear: A recent review of the literature identified seven studies and 28 case reports, which showed an increased mortality with the use of tumor necrosis factor-inhibitors (TNF-i) (63). In this analysis, female sex and longer disease duration were associated with ILD onset or worsening (63).…”
Section: Pulmonary Disease Patterns In Rheumatoid Arthritismentioning
confidence: 99%
See 1 more Smart Citation
“…Despite previous concerns over potential pulmonary toxicity with leflunomide, this agent also appears to be potentially beneficial for RA-ILD (62). In the setting of RA-ILD, the choice of biological therapy is not clear: A recent review of the literature identified seven studies and 28 case reports, which showed an increased mortality with the use of tumor necrosis factor-inhibitors (TNF-i) (63). In this analysis, female sex and longer disease duration were associated with ILD onset or worsening (63).…”
Section: Pulmonary Disease Patterns In Rheumatoid Arthritismentioning
confidence: 99%
“…In the setting of RA-ILD, the choice of biological therapy is not clear: A recent review of the literature identified seven studies and 28 case reports, which showed an increased mortality with the use of tumor necrosis factor-inhibitors (TNF-i) (63). In this analysis, female sex and longer disease duration were associated with ILD onset or worsening (63). The heterogeneity in the reported outcome measures was too large to draw any firm conclusions.…”
Section: Pulmonary Disease Patterns In Rheumatoid Arthritismentioning
confidence: 99%
“…[23] According to data obtained from the British Society of Rheumatology Biologics Register, the mortality rate from ILD in patients with rheumatoid arthritis (RA) treated with TNF-α inhibitors was similar to those treated with conventional DMARDs. [22] A recent review by Huang et al [24] highlighted that the use of TNF-α inhibitors in patients known to have RA-associated ILD may predispose them to more severe symptoms and even death. [24] While TNF-α inhibition has been used successfully to treat noninfectious granulomatous diseases, paradoxically TNF-α antagonism has also been associated with the development of a granulomatous, sarcoid-like disease, which may have both pulmonary and extra-pulmonary effects.…”
Section: Tumour Necrosis Factor Inhibitorsmentioning
confidence: 99%
“…Adalimumab wird subkutan verabreicht, die übliche Dosis beträgt 40 mg pro Woche. Die Rolle der TNF-α-Blockade bei anderen Autoimmun-ILD ist noch ungeklärt, doch eine aktuelle Übersichtsarbeit zur TNF-α-Blockade bei RA-ILD ergab eine hohe Rate von Nebenwirkungsmeldungen (87,5%) und eine berichtete Mortalität von 35% bei geringer Evidenz von potenziellem Nutzen in dieser Patientenkohorte, da es keine RCT gibt [102].…”
Section: Biologische Dmardunclassified